1491Impact of COVID19 on years of life lost with and without disability across 18 European-countries. (2nd September 2021) - Ahmadi-Abhari, Sara; Bandosz, Piotr; Kivimaki, Mika; Middleton, Lefkos
Abstract: Background: To accurately assess the impact of COVID19 on life-expectancy, years of life lost, and prevalence of dementia and disability, a model integrating calendar-trends in cardiovascular-disease, dementia, disability and mortality is required. We estimated these impacts in Austria, Belgium, Czech-Republic, Denmark, Estonia, France, Germany, Greece, Hungary, Italy, The Netherlands, Poland, Portugal, Slovenia, Spain, Sweden, Switzerland, and the UK. Methods: Data to inform the ten-state Monte-Carlo Markov-model for the 18 European countries were derived from official-statistics for population-numbers and mortality-rates (age&sex-specific) and from Survey for Health, Ageing and Retirement in Europe for prevalence-estimates and transition-probabilities. Impact of COVID19 was measured comparing the estimates derived from incorporating expected mortality rates assuming calendar-trends in mortality and incidence of dementia, disability, and cardiovascular-disease continue those of the past two-decades, and those incorporating excess COVID19 mortality. Results: Assuming COVID-19 vaccination and termination of the pandemic will be accomplished by the end of 2021, the pandemic will have resulted in a loss of 9.3M (95% Uncertainty-Interval 1.3M-29.8M) person-years of life, including 7.1M person-years of dementia-free life and 5.2M person-years of disability-free life among the 289M population (as of 2019) above age-35. The effects on prevalence of dementia, disability and life-expectancy will be presented. Conclusions: The impact of the pandemic on disability-free person-years of life lost are devastating, marking a need for more rapid actions to halt the spread of epidemics. Key messages: Accurate estimation of future prevalence of dementia and disability to quantify the impact of the pandemic on years of life lost needs to simultaneously account for the declining trends in incidence of dementia and the decline in cardiovascular disease incidence and mortality resulting in increased life-expectancy and a larger pool susceptible to dementia and disability. The COVID19 pandemic is estimated to result in 9.3million person-years of life lost in 18 European countries including a loss of 7.1M person-years of dementia-free life and 5.2M person-years of disability-free life.